Bengala inteligente: um modelo para apoio à navegação de deficientes visuais baseado em reconhecimento de cores. - BARBOSA, Luiz Carlos de Souza (Universidade Federal do Pará, 2020)
This work presents the project to develop a navigation support system for the visually impaired, based on the proposal to use a cane with electronic devices and a mobile device, aiming to help the visually impaired to find sectors and to move autonomously in a environment mapped. Mapping takes place through the implantation of bands with different colors at strategic points, where each color group identifies the sector in which it is implanted. Once mapped, it will be possible to navigate the nvironment with the support of the cane equipped with an RGB sensor for color collection, a vibration motor for tactile feedback, and a microcontroller with Wi-Fi module to connect to the mobile device. According to the respective set of colors captured by the sensor, the user receives information corresponding to a location, route or object by voice. To verify the applicability, two maps were implanted, one in internal and one external environment. Functional evaluations were performed with the support of a group of volunteers who made the route using the device. As results, qualitative data were presented of the system functionalities, collected during the experiments, through observation of the behavior of the system and application of questionnaires to the users.